Estrogens ameliorate remote organ inflammation induced by burn injury in rats - (:unkn) unknown (BIRKHAUSER VERLAG AG, 2001)
Objective and design: The present study was designed to investigate the role of sex steroids in burn-induced remote organ injury. Material or subjects: Male Wistar albino rats were given burn trauma (n=39), and underwent castration or sham operation at 2 h following the burn injury. Treatment. Rats were injected sc with either 17beta estradiol benzoate (E(2), 10 mg/kg) or an androgen receptor blocker cyproterone acetate (CPA, 25 mg/kg) or vehicle, immediately after burn and at 12 h. Methods: At 24 h of burn insult, rats were decapitated. Blood samples for RIA of testosterone, estradiol and tumor necrosis factor (TNF)-alpha and the tissue samples for myeloperoxidase activitiy (MPO) were taken. ANOVA student's t test was used for statistical analysis. Results: Castration, antiandrogen and E, treatments increased plasma estradiol levels and depressed burn-induced elevation in serum TNF-alpha levels. In the liver and lung, burn-induced increase in MPO was reduced by E, and castration, while CPA was effective in reducing neutrophil infiltration only in the liver. Conclusion: We propose that treatment with estrogens or antiandrogens might be applicable in clinical situations to ameliorate systemic inflammation induced by burn.
Keywords: castration; androgen depletion; estradiol; myeloperoxidase activity; A(2) RECEPTOR DENSITY; THERMAL-INJURY; TRAUMA-HEMORRHAGE; TESTOSTERONE; RESUSCITATION; MALES; SEX; ATHEROSCLEROSIS; INVOLVEMENT; REPERFUSION